Inflation and deflation pressure-volume loops in anesthetized pinnipeds confirms compliant chest and lungs - Fahlman, Andreas; Loring, Stephen H.; Johnson, Shawn P.; Haulena, Martin; Trites, Andrew W.; Fravel, Vanessa A.; Van Bonn, William G. (Frontiers in Physiology, 2014)
We examined structural properties of the marine mammal respiratory system, and tested Scholander’s hypothesis that the chest is highly compliant by measuring the mechanical properties of the respiratory system in five species of pinniped under anesthesia (Pacific harbor seal, Phoca vitulina; northern elephant seal, Mirounga angustirostris; northern fur seal Callorhinus ursinus; California sea lion, Zalophus californianus; and Steller sea lion, Eumetopias jubatus). We found that the chest wall compliance (CCW) of all five species was greater than lung compliance (airways and alveoli, CL) as predicted by Scholander, which suggests that the chest provides little protection against alveolar collapse or lung squeeze. We also found that specific respiratory compliance was significantly greater in wild animals than in animals raised under human care. While differences in ages between the two groups may affect this incidental finding, it is also possible that lung conditioning in free-living animals may increase pulmonary compliance and reduce the risk of lung squeeze during diving. Overall, our data indicate that compliance of excised pinniped lungs provide a good estimate of total respiratory compliance.